Digital transformation in higher education institution management: key aspects for blockchain adoption - Dalla Rosa, Rafael; Verschoore, Jorge Renato; Kinast de Camillis , Patricia (Cuadernos de Administración, 2026)
The article presents a framework that highlights the relationships between key aspects related to digital transformation through blockchain in the context of Higher Education Institution management. We developed this framework using the Design Science Research methodology, which involved three validation phases and 23 interviews. A total of 16 key aspects were identified, namely: IT Governance, change mapping, internal and external motivations, organizational culture, change in value creation, structural changes, financial aspects, digital strategies, regulatory frameworks, adoption of technologies, types of approach (student and/or institution-centered), safety standards, interoperability of transactions, auditability, authenticity, and decentralization. This study contributes not only to the identification and description of these key aspects within the context of Higher Education Institutions but also to overcoming the traditional teaching/learning approach when it comes to the adoption of technologies in Higher Education Institutions, including elements for their organizational management.